2016
DOI: 10.1159/000445766
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Dermatosis in a Patient with Anaplastic Large-Cell Lymphoma: Case Report and Literature Review

Abstract: Background/Aims: Paraneoplastic dermatoses are skin disorders that are associated with malignancy. Anaplastic large T-cell lymphoma (ALTCL) has rarely been associated with paraneoplastic skin manifestations such as gangrenous foot ulcers and erythroderma. Methods: We describe a case of ALTCL presenting as a large annular skin rash. The clinical picture, course, and treatment will be discussed along with current hypotheses on the mechanism of paraneoplastic syndromes. Results: Skin manifestations in ALTCL most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Less commonly, paraneoplastic erythroderma is associated with acute myeloid leukaemia and solid tumours [7,8]. Paraneoplastic erythroderma associated with systemic lymphoma is exceptionally rare.…”
Section: Discussionmentioning
confidence: 99%
“…Less commonly, paraneoplastic erythroderma is associated with acute myeloid leukaemia and solid tumours [7,8]. Paraneoplastic erythroderma associated with systemic lymphoma is exceptionally rare.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous manifestations linked to melanoma are scarce and of unknown underlying mechanism. The diagnosis is of exclusion and should meet the criteria of Curth's postulates [ 5 ]. The best documented dermatoses in relation are dermatomyositis and pemphigus vulgaris [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Various studies have demonstrated the incidence of this relatively rare disorder; a study in an Indian population documented incidence around 35 per 100,000 dermatology patients, 3 and a study of a Chinese population with incidence around 13 per 100,000 dermatology patients. 4 The causes of erythroderma include exacerbation of existing/underlying dermatoses (such as psoriasis, atopic dermatitis, pemphigus), cutaneous drug eruptions 5 and malignancy-related erythroderma either from paraneoplastic causes (representing particular cutaneous manifestations of an underlying malignancy without infiltration of malignant cells 6 ) or from primary cutaneous malignancies such as mycosis fungoides, Sézary syndrome and adult T-cell leukaemia/lymphomas. 7 Despite malignancy-related erythroderma constituting only a small fraction of erythroderma cases, 8 clinical implications on diagnosis and surveillance can be profound.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of erythroderma include exacerbation of existing/underlying dermatoses (such as psoriasis, atopic dermatitis, pemphigus), cutaneous drug eruptions 5 and malignancy‐related erythroderma either from paraneoplastic causes (representing particular cutaneous manifestations of an underlying malignancy without infiltration of malignant cells 6 ) or from primary cutaneous malignancies such as mycosis fungoides, Sézary syndrome and adult T‐cell leukaemia/lymphomas 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation